The French symphony at the fin de siècle : style, culture, and the symphonic tradition - Deruchie, Andrew, 1971- (Eastman studies in music, 2013)
In this first full-length study of the symphony in late nineteenth- and early twentieth-century France, Andrew Deruchie provides extended critical discussion of seven of the most influential and frequently performed works of the era, by Camille Saint-Saëns, César Franck, Édouard Lalo, Vincent d'Indy, and Paul Dukas. The volume explores how these symphonists modernized the art form yet preserved many of the formal and rhetorical conventions of the canon, reconciling, in particular, Beethoven's symphonic legacy with the musical culture, intellectual environment, and political milieu of fin-de-si.